Vacuoles from Sugarcane Suspension Cultures : II. CHARACTERIZATION OF SUGAR UPTAKE - Thom, Margaret (1982)
Vacuoles, isolated from sugarcane (Saccharum sp.) cells, took up 3-O methylglucose and sucrose and the evidence suggests specific transport systems for these sugars. There was no evidence of sugar efflux from preloaded vacuoles. Vacuoles in situ accumulated 3-O methylglucose, sucrose, glucose, and fructose, as shown by incubation of protoplasts with labeled sugar and subsequent analysis of vacuolar and cytoplasmic radio-activity. During the initial minutes of incubation, the amount and concentration of labeled sugar was higher in the cytoplasm than in the vacuole, but subsequently there was active uptake and accumulation into the vacuole. The rate of hexose transfer into the vacuole in situ approached that of hexose uptake by isolated vacuoles; however, the rate of sucrose uptake by isolated vacuoles was below the in situ rate. The site of sucrose synthesis was in the cytoplasm.